Angel Ferrant and the Vienna School of Arts - Ortega Cubero, Inés (Pulso. Revista de educación, 2009)
In this article we describe the organization of the Kunstgewerbeschule in Viena and the didactic methodology that it developed from the artistic movement known as Secession, making it in one of the most modern schools in all of Europe. These methods infl uenced the Spanish sculptor and teacher Ángel Ferrant, who visited it in 1927 and later became one of the most innovative art teachers in Spain. During his visit, he was especially impressed by the work of Professor Franz Cizek, a famous specialist in teaching children, and by the work of Sculpture Professor Eugen Steinhof.
Keywords: Vienna Art Nouveau; Shape Analysis; Spontaneous Self-Expression; Childhood; Pottery-Making